Implementasi Supervisi Akademik Dengan Teknik Coaching Dalam Meningkatkan Mutu Pembelajaran - Sisean Baga; Taufiqurrahman Taufiqurrahman; Fuat Alfauzi; Winda A. Cahyaningrum (Lembag, 2024)
This research aims to increase teachers' performance which impacts learning quality through the implementation of academic supervision with the coaching technique. The research method used is the School Action Research through the descriptive quantitative approach. The data-gathering technique was done via interviews, observation, and checklists from learning equipment documents. The result of the research shows that academic supervision on cycle 1 (85,7) is in the good category, and cycle 2 (90,9) is in the very good category. This shows there is an improvement of score on the type of administrative supervision and class supervision compared to pre-cycle (79,4) with the good category. This result was able to be reached due to a change in academic supervision, which was the inclusion of pre-observation, observation, and post-observation as well as a dialogue process with the coaching technique, which increased the quality of teachers in the learning process. The strengthening of coaching and the addition of follow-ups on cycle II caused the academic supervision score of teachers to increase more. The academic supervision stage and coaching technique allows teachers to dig for potentials further and causes them to be more prepared when an observation by the headmaster is done. Academic supervision with the coaching technique must always be familiarized for the improvement of teacher’s quality in school. The need for continuous monitoring and consistent implementation of academic supervision becomes a unique challenge to increase the teachers' performance, which impacts learning quality in class.